Flotation Recovery of Fine Slime Cassiterite from Gravity Tailings - Jiang XING; Jiushuai DENG; Hao ZHANG; Tichen WANG; Yan HUANG; Bozeng WU (Kuangchan zonghe liyong)
The concentrator of Dachang mining area in Guangxi adopts the method of shaking table gravity separation to recover cassiterite in production, which has problems such as difficult cassiterite separation and large loss of fine mud. In order to strengthen the recovery of fine-grained cassiterite in tailings, the flotation test of cassiterite fine mud recovery was carried out on the tailings obtained from the shaking table gravity separation of the concentrator. The test results show that through the technological process of flotation “pre-desulfurization and cassiterite flotation”, on the basis of conditional tests, 2 000 g/t collector, 800 g/t activator and 6 g/t defoamer were used for the tin flotation test. The tin concentrate with a tin grade of 7.41% and a recovery rate of 47.61% was obtained in the closed-circuit test, and the index is good and economical.